2017
DOI: 10.1159/000475772
|View full text |Cite
|
Sign up to set email alerts
|

Increased Visfatin Expression Is Associated with Nuclear Factor-κB in Obese Ovalbumin-Sensitized Male Wistar Rat Tracheae

Abstract: Objective: To investigate the effects of diet-induced obesity on the expression of nuclear factor-κB (NF-κB) and visfatin messenger RNA in male Wistar rats' tracheae after sensitization with ovalbumin (OVA). Materials and Methods: Twenty male Wistar rats were divided into 4 groups (n = 5 for each group), which included a control group fed a normal diet (ND) and groups fed normal diet, OVA-sensitized (S+ND); high-fat diet (HFD) only (diet-induced obesity); and high-fat diet, OVA-sensitized (S+HFD). All animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…In DIO groups, serum levels of TG, TC, LDL, and HDL were remarkably increased compared with those in the normal diet groups, indicating the occurrence of hyperlipidemia, which was similar to previous studies [45,46]. Given that it has been shown that free fatty acids can activate inflammatory pathways in tissues [7], the authors do not rule out the effect of lipid profiles in alteration of cellular pathways. Increasing the miRNA-146a as well as NF-kB in the current study and there was the association between miRNA-146a with lipid profile, at least in part, reflects the fact that free fatty acids may have been involved in these pathways, which requires further studies.…”
Section: Figsupporting
confidence: 83%
See 2 more Smart Citations
“…In DIO groups, serum levels of TG, TC, LDL, and HDL were remarkably increased compared with those in the normal diet groups, indicating the occurrence of hyperlipidemia, which was similar to previous studies [45,46]. Given that it has been shown that free fatty acids can activate inflammatory pathways in tissues [7], the authors do not rule out the effect of lipid profiles in alteration of cellular pathways. Increasing the miRNA-146a as well as NF-kB in the current study and there was the association between miRNA-146a with lipid profile, at least in part, reflects the fact that free fatty acids may have been involved in these pathways, which requires further studies.…”
Section: Figsupporting
confidence: 83%
“…To calculate the obesity indices in the rodents, factors such as final body weight, percentage of body fat (BF%), and Lee index were determined. The following formula indicates the calculation of all the obesity indices : Percentage of body weight changes (%) = [(Final weight ‐ initial weight)/ initial weight] × 100 Lee index (mg/mm) = Final weight 0.33 / naso‐anal length Percentage of body fat (%) = 0.69 (Lee index‐274.8) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that visfatin, one of the adipocytokines, in lung tissue increases in obesity associated with the OVAsensitization condition. 32 The accumulation of inflammatory cytokines along with systemic inflammation in obesity situation may have affected airway responsiveness, which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the activated form of NF-κB induces the transcription of various catabolic factors, MMPs, ADAMTS, cytokines and chemokines, pro-inflammatory mediators, and contributes to the degradation of collagen and proteoglycans [74,75]. Different studies showed that visfatin and resistin induce the activation of the NF-κB signaling pathway [41,76,77,78,79]. In agreement with the current literature we demonstrated a significant increase of the expression, activation, and in turn of the nuclear translocation of the NF-κB p50 subunit in OA chondrocytes incubated by visfatin and resistin.…”
Section: Discussionmentioning
confidence: 99%